Adaptive thermal comfort study of workers in a mini-industrial unit during summer and winter season in a tropical country, India. (15th June 2021) - Kumar, Sanjay; Mathur, Anuj; Singh, Manoj Kumar; Rana, K.B.
Abstract: Providing a comfortable thermal environment to workers for better health and productivity is one of the necessary conditions for sustainable industrial development. However, there is a dearth of field studies on the thermal comfort status and adaptation of workers in naturally ventilated industrial buildings across the world. Therefore, an adaptive thermal comfort field study in a mini-industrial unit factory, located in the composite climate of India, was conducted in the hot summer and cold winter seasons. Overall, 1276 valid subjective responses were collected from 325 factory workers during the field measurements and survey. We found a seasonal comfort temperature variation of more than 9.5°C with a mean comfort temperature of 32.2°C. The mean preferred temperature was observed about 2.5°C lower than their mean comfort temperature. The adaptive comfort relation suggested that surveyed factory workers had a high thermal adaptation owing to the combined effect of behavioural adjustments and elevated airspeed. A logistic regression analysis was carried out to predict the fan use behavior by the workers during the hot summer season. Since the study duration also lies in the COVID-19 pandemic period, an effort has been made to quantify the psychological and behavioural changes of workers due to the COVID-19 pandemic situation at their workplace through a questionnaire-based study. Graphical abstract: Image 1 Highlights: Adaptive thermal comfort and comfort preference study of Indian factory workers. Seasonal comfort and preferred temperature varied more than 9.5 °C and 7.9 °C, respectively. Workers were found more adaptive compared to subjects in offices and residential buildings in India. 48% of workers reported significant decrease in their work productivity after the COVID-19 pandemic.